Особенности решений одного класса уравнений механики сплошных сред - Ильман, В.М.; Капустян, В.Е. (Український математичний журнал, 2003)
Проведено аналіз одного класу сімей інтегральних рівнянь, одержано залежності особливостей розв'язків інтегральних рівнянь під розміру сімей ядер рівнянь і на цій основі запропоновано методику побудови наближених розв'язків для малого параметра. We analyze one class of families of integral equations and describe the dependence of the singularities of solutions of integral equations on the dimensions of the families of kernels of equations. On the basis of these results, we propose procedures for the construction of approximate solutions for a small parameter.